Lecture and Demonstration Methods as Islamic Education Teachers' Efforts to Improve Student Behavior Development at SMK Negeri 5 Telkom Banda Aceh - Amiruddin; MY, Yusnawati (Jurnal Pendidikan Profesi Guru, 2025)
This research is motivated by the low quality of student behavior in class X of SMKN 5 Telkom Banda Aceh. One of the steps that needs to be taken by teachers in the field of PAI study is to conduct student coaching in a sustainable manner by emphasizing discipline and obedience through literacy and Islamic stories. The purpose of this study is to find out the efforts of PAI teachers in improving student behavior coaching, including the steps and factors that affect teachers in the process. This classroom action research aims to see the extent to which student behavior coaching at SMKN 5 Telkom Banda Aceh is improved by applying learning strategies through lecture and demonstration methods. The use of this method is applied in the form of Class Action Research (PTK) with a descriptive-qualitative approach. Data collection techniques are carried out through observation, interviews, and documentation, and are carried out in four stages, namely planning, implementation, observation, and reflection. This research uses a type of classroom action research which aims to research and improve the quality and professionalism of teachers in managing the learning process so that learning goals can be achieved.